Study on the Dynamic Data Acquisition Method of Poly-rib Belt - Wang Enjun; Xiao Jun; Liao Yide; He Chao; Lei Jinyu (Jixie chuandong)
Because of the optimal design of ploy-rib belt plays an important role in improving the performance of the car,obtaining and analyzing ploy-rib belt motion information is becoming the hotspot studied by researchers. For the shortage that the poly-rib belt need be simplify existed in the dynamic modeling and simulation,the digital image processing techniques are adopted to obtain the dynamic information of engine ploy-rib belt. Firstly,a camera is applied in tracking and recording the artificial marking signs on the ploy-rib belt. Secondly,the location information of the making signs is acquired by digital image processing techniques. At last,the marking signs that have become several kinds of typically deformable are recognized by using the this algorithm and Hough transform detection method,then comparing the errors between the two methods and analyzing correlation of the dynamic data which is obtained by the experiment and the laser rangefinder. The experiment results show that the dynamic information on engine ploy-rib belt can be obtained precisely by using the proposed method.